Longitudinal Rehabilitation of Binocular Function in Adolescent Intermittent Exotropia After Successful Corrective Surgery - Peng, Tingting; Xu, Meiping; Zheng, Fuhao; Zhang, Junxiao; Chen, Shuang; Lou, Jiangtao; Wang, Chunxiao; Wang, Yuwen; Yu, Xinping (Frontiers in Neuroscience, 2021)
Purpose To study the longitudinal rehabilitation of binocular visual function in adolescent intermittent exotropia (IXT) after successful surgery and compare the results with those of a normal population. The role of binocular function in ocular alignment stability was also evaluated postoperatively. Methods In this prospective study, 30 adolescents with IXT successfully corrected after 1 month were followed for 12 months, and 30 children with normal vision were enrolled as controls. Stereopsis, the fusional vergence amplitude, sensory fusion, and accommodative flexibility were measured to assess binocular function at baseline and 6 and 12 months postoperatively. The controls were tested once when they were enrolled in the study. Results The deviation was −32.00 ± 8.60 prism diopters (PD) at distance fixation and −36.0 ± 9.10 PD at near fixation preoperatively with an average correction of 28.53 ± 3.79 PD and 30.67 ± 1.34 PD at 1 month postoperatively. Distance stereoacuity and near stereoacuity improved from 1 to 12 months postoperatively (p = 0.025 and p = 0.041, respectively). Compared with the controls, the fusional convergence reserve at distance (p = 0.025) and near (p = 0.033) fixations and fusion reserve ratio at distance (p = 0.000) and near (p = 0.000) fixations remained subnormal, whereas sensory fusion (p = 0.237), distance stereopsis (p = 0.120), and the fusional divergence amplitude at a distance (p = 0.168) were normal. However, no significant correlations were found between binocular functions at 1 month postoperatively and the postoperative drift. Conclusion Binocular function significantly improved from before to after successful corrective surgery and continued to improve from 1 to 12 months postoperatively in adolescents with IXT. No significant correlations were found between binocular functions at 1 month postoperatively and ocular alignment stability.